Effectiveness of Video Teaching Programme on Knowledge Regarding Impact of Smartphone Dependence on Physical Health, Academics and Behavior among Adolescents Studying in Selected in Junior Colleges - Bipasha Sharma1, Sheetal Barde2, Merlin Suji3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Mobile phone use has become very common in today’s world. Though it is very handy and we can connect inany part of the world there are also number of health issues. The study purposes to ascertain the knowledgelevel about smartphone’s dependence impact on physical health academics and behavior among adolescentsstudying in junior colleges. Design used for the purpose of the study was Single set pre-test post-test.Sampling technique used for the selection of participants was Probability Random. To select the sampleRandom sampling technique was used. After the pre-test, intervention was planned followed by post-test wasdone after 1 week. Result shows that there was effectiveness of video teaching Programme on knowledge.